ATONISHING [CO2SO3H]-: CARBONATO AND SULFITO NEW ADDUCTS DERIVING FROM THE INTERACTIONS BETWEEN R4NCO2SO3H (R=Et, Me) AND HgX2, SnX4 (X=Cl, Br), SbCl5 - DINORA DE BARROS; LIBASSE DIOP (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
In ethanol, a C-S cleavage occurs in final products on allowing R4NCO2SO3H – R = Me, Et - to react with HgX2, SnX4 (M = Hg, X= Cl, Br), leading to carbonate and sulfite adducts and complexes ,infrared study of which have been carried out, then structures suggested on the basis of spectroscopic data. When (Me4N)CO2SO3H is allowed to react with SbCl5, HgX2 (X = Cl, Br), sulfite adducts were obtained, studied by infrared. The suggested structures are discrete, the sulfite anion behaving as a bidentate ligand.